Pengaruh Model Pembelajaran Terhadap Peningkatan Kemampuan Pemecahan dan Kemampuan Berpikir Kreatif Matematika - Khairil Amri; Virgana Virgana; Irwan Agus; Asep Sahrudin (Universitas Mathla'ul Anwar Banten, 2026)
This study aims to determine: 1) The influence of perceptions of teacher pedagogical competence and self-efficacy together on mathematics learning achievement of State Vocational High Schools in Pandeglang Regency. 2) The influence of perceptions of teacher pedagogical competence on mathematics learning achievement of State Vocational High Schools in Pandeglang Regency. 3) The influence of self-efficacy on mathematics learning achievement of State Vocational High Schools in Pandeglang Regency. The method used in this study is a survey with correlational analysis techniques. The population in this study was 631 students and a sample of 158 students. The results of the study show: 1) There is a significant influence of perceptions of teacher pedagogical competence and self-efficacy together on mathematics learning achievement of State Vocational High School students in Pandeglang Regency. This can be proven by the value of Sig = 0.000 <0.05 and F count 42.900. 2) There is a significant influence of perceptions of teacher pedagogical competence on mathematics learning achievement of State Vocational High School students in Pandeglang Regency. This can be proven by the Sig value = 0.047 < 0.05 and t count = 2.003. 3) There is a significant influence of self-efficacy on mathematics learning achievement of State Vocational High School students in Pandeglang Regency. This can be proven by the Sig value of 0.000 < 0.05 and t count = 8.455 = 8.455